mRNA Levels of Related Abcb Genes Change Opposite to Each Other upon Histone Deacetylase Inhibition in Drug-Resistant Rat Hepatoma Cells - Sike, Ádám (Public Library of Science, 2014)
The multidrug-resistant phenotype of tumor cells is acquired via an increased capability of drug efflux by ABC transporters and causes serious problems in cancer treatment. With the aim to uncover whether changes induced by epigenetic mechanisms in the expression level of drug transporter genes correlates with changes in the drug resistance phenotypes of resistant cells, we studied the expression of drug transporters in rat hepatoma cell lines. We found that of the three major rat ABC transporter genes Abcb1a, Abcb1b and Abcc1 the activity of only Abcb1b increased significantly in colchicine-selected, drug-resistant cells. Increased transporter expression in drug-resistant cells results primarily from transcriptional activation. A change in histone modification at the regulatory regions of the chromosomally adjacent Abcb1a and Abcb1b genes differentially affects the levels of corresponding mRNAs. Transcriptional up- and down-regulation accompany an increase in acetylation levels of histone H3 lysine 9 at the promoter regions of Abcb1b and Abcb1a, respectively. Drug efflux activity, however, does not follow tightly the transcriptional activity of drug transporter genes in hepatoma cells. Our results point out the need for careful analysis of cause-and-effect relationships between changes in histone modification, drug transporter expression and drug resistance phenotypes.